2019
DOI: 10.1002/esp.4770
|View full text |Cite
|
Sign up to set email alerts
|

The impact of hydrograph variability and frequency on sediment transport dynamics in a gravel‐bed flume

Abstract: A laboratory study was undertaken to investigate how changes in flow regime and hydrograph shape (number of cycled hydrographs and duration of each hydrograph) together impact bedload transport and resulting bed morphology. Three hydrologic conditions (experiments) representing different levels of urbanization, or analogously different flow regimes, were derived from measured hydrometric field data. Each experiment consisted of a series of hydrographs with equal peak discharge and varying frequency, duration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…STR is a measure of the level of sediment storage within the flume, indicating erosive or depositional trends. Bedload hysteresis was calculated by evaluating the hysteresis ratio, which is defined as the ratio of total bedload transport on the rising limb to the total bedload transport on the falling limb (Juez et al 2018, Plumb et al 2019. The hysteresis ratio was then plotted against the large particle spacing ( / ) to determine any trends amongst the test cases.…”
Section: Sediment Transport Ratio and Bedload Hysteresismentioning
confidence: 99%
“…STR is a measure of the level of sediment storage within the flume, indicating erosive or depositional trends. Bedload hysteresis was calculated by evaluating the hysteresis ratio, which is defined as the ratio of total bedload transport on the rising limb to the total bedload transport on the falling limb (Juez et al 2018, Plumb et al 2019. The hysteresis ratio was then plotted against the large particle spacing ( / ) to determine any trends amongst the test cases.…”
Section: Sediment Transport Ratio and Bedload Hysteresismentioning
confidence: 99%
“…The results of many field and laboratory studies highlight how changes in the flow regime and hydrograph shape describe bedload transport and the resulting bed morphology [12][13][14][15]. Hassan and Church [15] highlighted that the hysteresis loops were more pronounced for hydrograms of longer durations, which corresponded to less instability until the peak discharge was reached.…”
Section: Discussionmentioning
confidence: 99%
“…The relation between flow activities and bedload transport rates has been highlighted by Arnborg et al [12] and Williams [13]. Both field and laboratory experiments indicated that discharge and bedload transport relationships can be analyzed on the basis of hysteresis loops [14]. They found that for long-existing and continuous sediment concentrations associated with a long flood, the relationship between bedload transport and discharge in the relationship diagram is represented by a figure eight with a clockwise loop for high flows and a counterclockwise loop for low flows.…”
Section: Introductionmentioning
confidence: 98%
“…It has been shown that the frequency of rainfall and their intensity significantly affect the load and size of soil particles implemented into rivers [52,53].…”
Section: Discussionmentioning
confidence: 99%